Primary healthcare expansion and mortality in Brazil's urban poor: A cohort analysis of 1.2 million adults. - Thomas Hone (PLoS Medicine, 2020)
Background Expanding delivery of primary healthcare to urban poor populations is a priority in many low- and middle-income countries. This remains a key challenge in Brazil despite expansion of the country's internationally recognized Family Health Strategy (FHS) over the past two decades. This study evaluates the impact of an ambitious program to rapidly expand FHS coverage in the city of Rio de Janeiro, Brazil, since 2008. Methods and findings A cohort of 1,241,351 low-income adults (observed January 2010-December 2016; total person-years 6,498,607) with linked FHS utilization and mortality records was analyzed using flexible parametric survival models. Time-to-death from all-causes and selected causes were estimated for FHS users and nonusers. Models employed inverse probability treatment weighting and regression adjustment (IPTW-RA). The cohort was 61% female (751,895) and had a mean age of 36 years (standard deviation 16.4). Only 18,721 individuals (1.5%) had higher education, whereas 102,899 (8%) had no formal education. Two thirds of individuals (827,250; 67%) were in receipt of conditional cash transfers (Bolsa Família). A total of 34,091 deaths were analyzed, of which 8,765 (26%) were due to cardiovascular disease; 5,777 (17%) were due to neoplasms; 5,683 (17%) were due to external causes; 3,152 (9%) were due to respiratory diseases; and 3,115 (9%) were due to infectious and parasitic diseases. One third of the cohort (467,155; 37.6%) used FHS services. In IPTW-RA survival analysis, an average FHS user had a 44% lower hazard of all-cause mortality (HR: 0.56, 95% CI 0.54-0.59, p < 0.001) and a 5-year risk reduction of 8.3 per 1,000 (95% CI 7.8-8.9, p < 0.001) compared with a non-FHS user. There were greater reductions in the risk of death for FHS users who were black (HR 0.50, 95% CI 0.46-0.54, p < 0.001) or pardo (HR 0.57, 95% CI 0.54-0.60, p < 0.001) compared with white (HR 0.59, 95% CI 0.56-0.63, p < 0.001); had lower educational attainment (HR 0.50, 95% CI 0.46-0.55, p < 0.001) for those with no education compared to no significant association for those with higher education (p = 0.758); or were in receipt of conditional cash transfers (Bolsa Família) (HR 0.51, 95% CI 0.49-0.54, p < 0.001) compared with nonrecipients (HR 0.63, 95% CI 0.60-0.67, p < 0.001). Key limitations in this study are potential unobserved confounding through selection into the program and linkage errors, although analytical approaches have minimized the potential for bias. Conclusions FHS utilization in urban poor populations in Brazil was associated with a lower risk of death, with greater reductions among more deprived race/ethnic and socioeconomic groups. Increased investment in primary healthcare is likely to improve health and reduce health inequalities in urban poor populations globally.